The Voltage Control in Single-Phase Five-Level Inverter for a Stand-Alone Power Supply Application Using Arduino Due - Daniel Santoso; Leonardus Heru Pratomo (Journal of Robotics and Control (JRC), 2021)
In the era of industrial revolution 4.0 expanded digital transformation, such as inverters. The principle of the inverter is to change the DC source to the AC source. The device using an AC source needs a voltage source that is controlled. Hence, the voltage source that is controlled is usually generated from a stand-alone power supply. The stand-alone power supply usually used a conventional inverter. The conventional inverter uses high frequency switching to obtain lower distortion harmonic in output voltage. Another solution is using a five-level inverter that has fewer power switches. The purpose in these research is to make a stand-alone power supply using a single-phase five-level inverter asymmetric topology, which has five power switches to control voltage output based on the standard of IEEE 519. The inverter does sinusoidal pulse width modulation on two the signal reference that was shifting 180 degrees toward the carrier signal. That research has been simulated using Power Simulator software and has been implemented in the laboratory. According to the result of simulation and implementation are generated voltage THD value amount of 4.39%.